Review of promotion of physical activity and health-related factors during pandemic for children and adolescents - Haemi Jee (Tehran University of Medical Sciences, 2021)
Background: Regularly performed physical activity promote proper development and prevent health risk factors in children and adolescents. Pandemic crisis has been limiting the scope of movement with social distancing for participation of physical activity for health promotion. This study aimed to review studies on promoting physical activity to prevent health risks for children and adolescents since the onset of COVID-19.